Transnational business feminism: Exporting feminism in the global economy. Issue 8 (27th September 2018) - Fodor, Éva; Glass, Christy; Nagy, Beáta
Abstract : Business feminism is a brand of feminism that privileges women's advancement in the corporate hierarchy and centres corporations as the ultimate purveyors of gender equity. While scholars have critiqued this formulation, little empirical research has analysed the processes that guide the dissemination and translation of business feminism in organizational settings within global corporate networks. This article advances scholarship on the global processes that drive the export of business feminism logics. We analyse the process of dissemination of business feminism from the headquarters of multinational corporations to corporate hubs located in Hungary. This process relies on women executives who are charged with translating policies and practices originating in the headquarters of western corporations. In‐depth interviews with women executives charged with implementing corporate policies reveal the ways in which business feminism is interpreted, modified and/or resisted by actors within organizational settings.